Beam and target parameters measurement system on helium ions linear accelerator - Anokhin, R.A.; Dubnyuk, S.N.; Dyachenko, A.F.; Kobets, A.P.; Manuilenko, O.V.; Pavlii, K.V.; Shevchenko, A.S.; Soshenko, V.A.; Tishkin, S.S.; Zabotin, A.V.; Zajtsev, B.V.; Zhuravlyov, A.V. (Вопросы атомной науки и техники, 2018)
A system for measuring beam and target parameters on helium ions linear accelerator is presented. The measurement system consists of sensors set, signal converters and computer with codes for processing experimental data.
The measurement system is designed for recording, visualizing, storing and processing data directly when samples
are irradiated with helium ions with energies of 0.12…4 MeV. The sample temperature, the ion beam current and its
shape, the sample tilt angle to the beam axis, the irradiation dose, the ionization, damage and helium range profiles
are measured/calculated. Наведено опис системи вимірювання параметрів пучка і мішені на лінійному прискорювачі іонів гелію.
Система вимірювань складається з набору датчиків, конвертерів сигналів і ЕОМ з програмою обробки експериментальних даних. Система вимірювань призначена для реєстрації, візуалізації, збереження і обробки
даних безпосередньо при опроміненні зразків іонами гелію з енергіями 0,12…4 МеВ. Вимірюються/обчислюються: температура зразка, струм і форма струму пучка іонів на зразку, кут нахилу зразка до осі
пучка, доза опромінення, профілі іонізації, пошкоджуваності і залягання гелію в зразку. Приведено описание системы измерения параметров пучка и мишени на линейном ускорителе ионов гелия. Система измерений состоит из набора датчиков, конвертеров сигналов и ЭВМ с программой обработки
экспериментальных данных. Система измерений предназначена для регистрации, визуализации, сохранения
и обработки данных непосредственно при облучении образцов ионами гелия с энергиями 0,12…4 МэВ. Измеряются/вычисляются: температура образца, ток и форма тока пучка ионов на образце, угол наклона образца к оси пучка, доза облучения, профили ионизации, повреждаемости и залегания гелия в образце.